2003
DOI: 10.1071/ea02198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing method and fertiliser inputs on the productivity andsustainability of phalaris-based pastures in Western Victoria

Abstract: The effects of combinations of different fertiliser rates and grazing methods applied to phalaris-based pastures on an acid, saline, yellow sodosol on the Dundas Tablelands of western Victoria (mean annual rainfall 623�mm) were measured from 1997 to 2000. The objective was to help identify management systems that improve phalaris growth and persistence, water use, and animal production, and thereby the productivity and sustainability of grazing systems. Pastures were either set stocked with low [mean 6.4 kg ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…At the commencement of the trial, the target stocking rates set for the farmlets were 7.5 dry sheep equivalents (DSE)/ha for farmlet B (considered by Cicerone members to be a typical stocking rate for the area) and 15 DSE/ha for both farmlets A and C. In spite of these targets being set at the beginning of the trial, it was agreed that stocking rate would be an emergent property of each farmlet in common with the approach of other researchers (Chapman et al 2003). It is important to point out that the grazing management treatments examined here represented two different forms of rotational grazing: one flexible (farmlets A and B) and the other intensive (farmlet C).…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the commencement of the trial, the target stocking rates set for the farmlets were 7.5 dry sheep equivalents (DSE)/ha for farmlet B (considered by Cicerone members to be a typical stocking rate for the area) and 15 DSE/ha for both farmlets A and C. In spite of these targets being set at the beginning of the trial, it was agreed that stocking rate would be an emergent property of each farmlet in common with the approach of other researchers (Chapman et al 2003). It is important to point out that the grazing management treatments examined here represented two different forms of rotational grazing: one flexible (farmlets A and B) and the other intensive (farmlet C).…”
Section: Treatmentsmentioning
confidence: 99%
“…Graham et al (2003) concluded that rotational grazing resulted in lower per head performance. Many researchers agree that rigid and inflexible grazing methods can restrict both animal and plant production (Norton 1998;Warn et al 2002;Chapman et al 2003;Graham et al 2003) but the size of the effect depends on seasonal conditions. Warn et al (2002) compared several grazing management treatments and concluded that optimum management depended on flexible, not fixed grazing intervals, based on the rate of plant growth; they also found no significant effect of grazing system or fertiliser level on wool cut per head or wool quality.…”
mentioning
confidence: 99%
“…The Cicerone experiment compared different grazing management systems to those studied by Chapman et al (2003). Whereas Chapman et al (2003) compared low and high rates of fertiliser application (6.4 and 25 kg P/ha.year, respectively), the Cicerone farmlet experiment was managed to achieve either moderate or high levels of soil fertility, based on soil tests.…”
Section: Integrative Discussionmentioning
confidence: 99%
“…Whereas Chapman et al (2003) compared low and high rates of fertiliser application (6.4 and 25 kg P/ha.year, respectively), the Cicerone farmlet experiment was managed to achieve either moderate or high levels of soil fertility, based on soil tests. For comparison, the annual rates of fertiliser applied to farmlets B and C were~4.9 and 4.3 kg P/ha, respectively, whereas farmlet A received~13.1 kg P/ha.year (Guppy et al 2013).…”
Section: Integrative Discussionmentioning
confidence: 99%
See 1 more Smart Citation